Analysis of degradation mechanisms in donor–acceptor copolymer based organic photovoltaic devices using impedance spectroscopy. (23rd September 2016) - Srivastava, S B; Sonar, P; Singh, S P
Abstract: The stability of organic photovoltaic (OPV) devices in ambient conditions has been a serious issue which needs to be addressed and resolved timely. In order to probe the degradation mechanism in a donor–acceptor polymer PDPP-TNT: PC71BM bulk heterojunction based OPV devices, we have studied current density–voltage ( J–V ) behavior and impedance spectroscopy of fresh and aged devices. The current–voltage characteristic of optimized fresh devices exhibit a short circuit current density ( J sc ) of 8.9 mA cm −2, open circuit voltage ( V oc ) of 0.79 V, fill factor (FF) of 54.6%, and power conversion efficiency (PCE) of 3.8%. For aged devices, J sc, V oc, FF, and PCE were reduced to 57.3%, 89.8%, 44.3% and 23.7% of its initial value, respectively. The impedance spectra measured under illumination for these devices were successfully fitted using a CPE-based circuit model. For aged devices, the low-frequency response in impedance spectra suggests an accumulation of the photo-generated charge carriers at the interfaces which leads to a significant lowering in fill factor. Such degradation in device performance is attributed to the incorporation of oxygen and water molecules in devices. An increase in the recombination resistance indicates a deterioration of free charge carrier generation and conduction in devices.